Analisis Stabilitas dan Kapabilitas Proses Spinning Benang Katun dengan Metode Six Sigma (Studi Kasus PT. Primissima) - Sahrial Amri; I Wayan Suletra; Fakhrina Fahma (Performa: Media Ilmiah Teknik Industri, 2005)
As a textile company which produces grey, PT. Primissima surely needs high quality yarn which is also produced in its factory as its main basic material. Decline in yarn quality that significantly happened on May until August 2004 causes negative effects to the company, especially in customer satisfaction. Analysis of process stability and capability is should be done to prove and explain the problem, particularly on the existing spinning III process. Analysis using Six Sigma method begins with identifying customer needs, then mapping customer needs into the critical to quality characteristics (CTQ), determining CTQ priority level based on customer importance rating and customer satisfaction rating, and last, measuring sigma value, process stabilityand process capability of the CTQ top priority level. The result that focused on unevenness yarn CTQ shows, with sigma value of 4.07 sigma, process condition isn’t stable and capable enough to meet the company’s specification target. From the process analysis is also obtained information that many factors like environment, machine, tool, process, material, employee, and measurement system are supposed causing the problem. Improvement and control suggestions are also given here.